System Dynamic Model of Measures for Reducing the Number of Road Accidents Due to Wrong-way Movement on Motorways - Topolšek, Darja; Lipičnik, Martin (Promet - Traffic&Transportation, 2012)
This paper provides a system dynamic model for reducing the number of motorway accidents due to wrong-way driving. Motorway accidents are often fatal due to high speeds. It is therefore necessary to carry out all the possible countermeasures in order to achieve adequate traffic management. One of the reasons for motorway accidents is driving in the wrong direction. Based on the analysis of the data on motorway accidents caused by driving in the wrong direction and based on the knowledge of individual project elements of junctions and slip roads, this paper will focus on this area. The possible countermeasures, presented here for preventing drivers from driving in the wrong direction on motorways drastically reduce the number of U-turn maneuvers that result in driving in the wrong direction and influence the level of safety on motorways. With the help of this model of system dynamics the countermeasures for reducing the number of such drivers will be confirmed and their effects will be shown.KEY WORDS: traffic safety, motorway, direction, (road) accidents, measures, system dynamics